Pengaruh Kompensasi, Lingkungan Kerja dan Motivasi Terhadap Kinerja Pada PT. Tonga Tiur Putra Pandangan Kabupaten Rembang. - Nurhidayati, Anik (potensio, 2008)
The study aims to examine the effect of compensation,work environment and motivation on performance in PT. Sonof Tonga Tiur view Rembang. The sample in this studyamounted to 75 respondents. The first hypothesis with thevalue t count> t table (2.115> 2.000) with significance level0.038 <0.05, means that there is significant influence of compensation(X1) to employee performance (Y). Testing thesecond hypothesis is the work environment variables (X2 )to employee performance (Y) can know the results of thecalculations whereas the t 3.818 2.000 t table at the 0.05 significancelevel (? = 0.05). Thus the significant effect of workenvironment (X2) on employee performance (Y). The thirdhypothesis tests the motivation variable (X3) on employeeperformance (Y) can be detected t count is greater than t2.058 2.000 table, at the level of significance is 0.05 ( ? =0.05), thus there is significant influence of motivation (X3) onemployee performance (Y). Hypothesis test kempat compensationvariable (X1) working environment (X2) and motivation(X3) jointly affect the performance of the employee(Y). Regression calculation is obtained f count> f table(12.765> 2.74) at 0.05 significance level> 0.00. Thus the threevariables (X1, X2, X3) jointly have a significant influence onemployee performance (as Y). Adjusted R2 value (coefficientof determination) indicates the variable compensation,work environment and motivation can explain the influenceof 32.3% on performance, while the rest equal to 67.7% explainedby other factors not included in this study.Keyword: compensation, work environment, motivation, performance